The Impact of Using Cashless Transactions Among Malaysian Consumers Towards Payment Systems Performance - Nursyazana Mohd Sapian; Siti Norziah Ismail (Research in Management of Technology and Business, 2021)
The rapid growth of technology has resulting to the changing of payment system method. The increase of the use of technology in payment system is due to fulfilling the Industry Revolution 4.0’s requirement. However, the lack of adoption and security are among several issues in the cashless transaction system. The objective of this research is to answer the research question which is to examine the relationship between the impact of cashless transaction and payment systems performance, to identify which antecedents of adoption are significant in diffusion of cashless transaction in Malaysia and to analyse most impactful antecedent of the cashless transaction towards payment systems performance. This study focuses on the impact of using the cashless transaction on the payment performance system that occurs among Malaysian consumers. This research employed a quantitative research design by using survey question and respondents was from 231 users of cashless payment system in Sungai Buloh. Descriptive analysis was used and discussed in the quantitative findings. The findings of this research found that there is significant relationship between the impact of cashless transaction towards payment systems performance and point out that facilitating condition was the most impactful factors.